2023
DOI: 10.1021/acs.jctc.3c00178
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of Excited Electronic States by Converging on Saddle Points Using Generalized Mode Following

Abstract: Calculations of excited electronic states are carried out by finding saddle points on the surface describing the variation of the energy of the system as a function of the electronic degrees of freedom. This approach has several advantages over commonly used methods especially in the context of density functional calculations, as collapse to the ground state is avoided, and yet, the orbitals are variationally optimized for the excited state. Such a state-specific optimization makes it possible to describe exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 132 publications
(267 reference statements)
0
20
0
Order By: Relevance
“…89−92 Even still, converging the required orbitals remains one of the challenges to 1C-NOCIS 2eOS but progress on this subject is active and we expect advances to further streamline this step. 93 As a concluding remark, we mention that localization of the core orbitals (when the canonical ground-state orbitals delocalize over several atoms) prior to the SCF re-optimization in the presence of a core hole is crucial for improvements in accuracy. 94 2.2.…”
Section: Adaptation Of 1c-nocis Model For a 2eos Referencementioning
confidence: 98%
See 1 more Smart Citation
“…89−92 Even still, converging the required orbitals remains one of the challenges to 1C-NOCIS 2eOS but progress on this subject is active and we expect advances to further streamline this step. 93 As a concluding remark, we mention that localization of the core orbitals (when the canonical ground-state orbitals delocalize over several atoms) prior to the SCF re-optimization in the presence of a core hole is crucial for improvements in accuracy. 94 2.2.…”
Section: Adaptation Of 1c-nocis Model For a 2eos Referencementioning
confidence: 98%
“…While converging high-energy core excited-state solutions is often difficult, there has been tremendous progress in the past decades. The techniques we employ for that purpose include the maximum-overlap methods, the state-targeted energy projection scheme, and square-gradient minimization, which provides a reliable suite of techniques to stabilize most core excited states. Even still, converging the required orbitals remains one of the challenges to 1C-NOCIS 2eOS but progress on this subject is active and we expect advances to further streamline this step . As a concluding remark, we mention that localization of the core orbitals (when the canonical ground-state orbitals delocalize over several atoms) prior to the SCF re-optimization in the presence of a core hole is crucial for improvements in accuracy …”
Section: Adaptation Of 1c-nocis Model For a 2eos Referencementioning
confidence: 99%
“…49,53 Preliminary studies show that the calculations can collapse to lower-energy solutions where the charge is too delocalized, giving an inadequate description of the excited state. 17,49 Moreover, even when MOM manages to prevent variational collapse, the convergence can still be problematic when using SCF algorithms based on the eigendecomposition of the Hamiltonian matrix, such as the direct inversion in the iterative subspace (DIIS). 51,54−58 Recently, direct orbital optimization (DO) methods have been developed for time-independent, variational excited state calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, one may optimize the orbitals for the excited state of interest (described with an appropriate reference), followed by a separate CI calculation, in a so-called state-specific approach (ΔCI). There has been a recent surge in the development of state-specific methods, covering single-reference and multiconfigurational self-consistent field, density functional theory, perturbation theory, quantum Monte Carlo, and coupled-cluster (CC) methods. In particular, by employing a minimal configuration state function (CSF) reference, we have recently shown that excitation-based ΔCI models deliver far more accurate excitation energies than their ground-state-based analogs …”
Section: Introductionmentioning
confidence: 99%